Addressing the Interprofessional Collaboration Competencies of the Association of American Medical Colleges: A Systematic Review of Assessment Instruments in Undergraduate Medical Education. (June 2016) - Havyer, Rachel D.; Nelson, Darlene R.; Wingo, Majken T.; Comfere, Nneka I.; Halvorsen, Andrew J.; McDonald, Furman S.; Reed, Darcy A.
Abstract : Purpose: To summarize characteristics and validity evidence of tools that assess teamwork in undergraduate medical education (UME), and provide recommendations for addressing the interprofessional collaboration competencies of the Association of American Medical Colleges (AAMC). Method: The authors conducted a systematic review, searching MEDLINE, MEDLINE In-process, CINAHL, and PsycINFO from January 1, 1979, through April 1, 2014; they searched reference lists and national meeting abstracts. They included original research reports that described a quantitative tool used to assess teamwork in UME. They abstracted characteristics and validity evidence for the tools, plus study quality, according to established frameworks. Two authors independently abstracted 25% of articles and calculated agreement. Authors then applied predefined criteria to identify tools best suited to address the AAMC's teamwork competencies. Results: Of 13, 549 citations, 70 articles describing 64 teamwork assessment tools were included. Of these 64 tools, 27 (42%) assessed teamwork in classroom, 31 (48%) in simulation, and only 7 (11%) in actual clinical settings. The majority (47; 73%) of tools assessed medical students' teamwork in interprofessional teams. On the basis of content concordance, strength of validity evidence, generalizability of scores, and level of outcomes, four published tools were recommended to assess the AAMC's teamwork competencies: the Collaborative Healthcare Interdisciplinary Relationship Planning Scale, Readiness for Interprofessional Learning Scale, Communication and Teamwork Skills assessment, and Teamwork Mini-Clinical Evaluation Exercise. Conclusions: Substantial validity evidence supports the use of several UME teamwork assessments. Four tools have been appropriately designed and sufficiently studied to constitute appropriate assessments of the AAMC's teamwork competencies. Abstract : Supplemental Digital Content is available in the text.